Advances in Chinese medicine-mediated AMPK/mTOR signaling pathway for the treatment of osteoporosis - Zhang Wenhao, Yi Lin, Xiang Wenyuan, Remira·Aimaiti, Deng Yingjie, Liao Jun, Liang Zhiquan, Li Leijiang, Fang Rui (Xin yixue, 2023)
Osteoporosis （OP） is a systemic bone disease and a common orthopedic disorder in elderly patients. High morbidity， disability and mortality rates and medical cost of OP bring huge burden to the patients and their family. Serine/threonine protein kinase（AMPK）/ mammalian target of rapamycin （mTOR） signaling pathway plays a significant role in cell metabolism and apoptosis. Traditional Chinese medicine monomer or compound can prevent and treat OP by regulating the expression levels of related factors through the AMPK/mTOR signaling pathway， whereas the specific mechanism remains elusive. In this article， the effect of AMPK/mTOR signaling pathway upon osteoblasts and osteoclasts， and the regulatory role of traditional Chinese medicine were reviewed， aiming to provide novel perspectives and ideas for prevention and treatment of OP.